2021
DOI: 10.3390/ijms22158061
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Nanoparticles: Evidence of Adverse Effects on the Male Reproductive System

Abstract: Metal oxide nanoparticles (MONPs) are inorganic materials that have become a valuable tool for many industrial sectors, especially in healthcare, due to their versatility, unique intrinsic properties, and relatively inexpensive production cost. As a consequence of their wide applications, human exposure to MONPs has increased dramatically. More recently, their use has become somehow controversial. On one hand, MONPs can interact with cellular macromolecules, which makes them useful platforms for diagnostic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 157 publications
(249 reference statements)
0
25
0
Order By: Relevance
“…Cumulative studies have shown that some adverse factors, such as new coronavirus [36], Marburg virus [37], chemotherapeutic drug busulfan [38], and heavy metal ion cadmium [39], can damage the BTB, resulting in spermatogenesis disorder and even male infertility. In addition, some studies have shown that some substances, such as manganese [40], nicotine and its metabolites in tobacco smoke [41], and metal oxide nanoparticles [42], can directly pass through the BTB and cause spermatogenesis disorder. Therefore, maintaining BTB integrity is an important basis for normal spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative studies have shown that some adverse factors, such as new coronavirus [36], Marburg virus [37], chemotherapeutic drug busulfan [38], and heavy metal ion cadmium [39], can damage the BTB, resulting in spermatogenesis disorder and even male infertility. In addition, some studies have shown that some substances, such as manganese [40], nicotine and its metabolites in tobacco smoke [41], and metal oxide nanoparticles [42], can directly pass through the BTB and cause spermatogenesis disorder. Therefore, maintaining BTB integrity is an important basis for normal spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Nr5A1 is a transcription factor that regulates the expression of steroidogenic genes like 3β-HSD in Leydig cells. Hence, some authors explored the influence of metal oxide NPs on the expression of genes related to steroidogenesis [99]. For instance, Hussein et al [100] reported that the intragastric administration of zinc oxide NPs (100 and 400 mg/kg b.wt) for 12 weeks significantly downregulated the expression of 17β-HSD, 3β-HSD, and Nr5A1 and simultaneously reduced the TES level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effects of direct mixing of the PVA (polyvinyl alcohol)-coated iron oxide nanoparticles with the sperm samples obtained from bovine were analyzed. When nanoparticles are reported to be entering the spermatozoid cells and then could get attached to their mitochondrial organelles inside their tails and also in their acrosomal regions inside their heads, there have been no direct impacts on spermatozoid acrosomal reactions and motilities ( Vassal et al, 2021 ).…”
Section: Nanotoxicology and Male Reproductive Systemsmentioning
confidence: 99%